Korelasi Antara Pengetahuan Teori Dan Kemampuan Praktik Penyiaran Mahasiswa KPI IAIN Parepare - Aisyah; Anugrah Nur Fitrah; Nurhalisa; Wahyuddin; Nurhakki (Communication and Islamic Broadcasting Studies IAIN Parepare, 2022)
Abstrak. Broadcasting is a familiar thing in society, many people are familiar with broadcasting but only look at the outside without understanding the parts inside broadcasting itself, in broadcasting there is theory and practice, these two things are very important and interrelated with each other. others, so for people, especially students who will or want to be involved in the world of broadcasting, especially for students who take majors related to broadcasting such as students of the KPI (Islamic Broadcasting Communications) IAIN Parepare study program, they must understand and master these two things, because One cannot practice broadcasting without understanding the theory first, because theory is the main thing and foundation before doing broadcasting practice. The ability to practice broadcasting can be seen how KPI IAIN Parepare students are able to realize and implement what they have learned and understood in the theoretical learning process, and they display these abilities and knowledge in the broadcasting practice process. This is based on the theory of Communication Skills, where this theory discusses the ability or quality of a person's communication performance. One theory that explains communication skills is skill acquisition theory. Each stage refers to information contained in long-term memory. Declarative information provided by basic memory for facts, while procedural information relates to events in the process of doing and doing something. Keywords : Theory, Practice, Broadcast